Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1210/endo.139.11.6305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Chicken Estrogen Receptor-α Messenger Ribonucleic Acid Isoforms Generated by Alternative Splicing and Promoter Usage**This work was supported by the Irish American Partnership (to C.G.), the Irish Cancer Society, and an EMBO long term fellowship (to G.F.).

Abstract: Using the rapid amplification of complementary DNA ends (RACE) methodology we have identified three new chicken estrogen receptor-␣ (cER␣) messenger RNA (mRNA) variants in addition to the previously described form (isoform A). Whereas one of the new variants (isoform B) presents a 5Ј-extremity contiguous to the 5Ј-end of isoform A, the two other forms (isoforms C and D) are generated by alternative splicing of upstream exons (C and D) to a common site situated 70 nucleotides upstream of the translation start s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 34 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…This study indicates that the mERα gene is transcribed from at least five different promoters. Even though the existence of several promoters of human, chicken and rat ERα genes has already been demonstrated [22,24,27,28], the sequences of mouse upstream exons have remained unknown so far. Various mRNA splice variants within the coding region of mouse ERα were reported [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study indicates that the mERα gene is transcribed from at least five different promoters. Even though the existence of several promoters of human, chicken and rat ERα genes has already been demonstrated [22,24,27,28], the sequences of mouse upstream exons have remained unknown so far. Various mRNA splice variants within the coding region of mouse ERα were reported [32].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other upstream exons in the ERα gene of human [24] and rat [25,26] were identified. Additionally, we have recently shown that the estrogen receptor α gene is transcribed from at least four promoters in chicken and from six promoters in human [27,28].…”
Section: Introductionmentioning
confidence: 99%